Pay the midwife! The cost of delivery in nineteenth-century rural West Flanders: the case of midwife Joanna Mestdagh - Matthys, Christa (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This article focuses on the determinants of the economic cost of at-home childbirth in Flanders in the nineteenth century. Literature on the remuneration of medical professionals in the nineteenth century is sparse. Yet the few existing studies show that fixed rates per delivery did not exist during the nineteenth century. Before that time, pricing was influenced by factors such as the professional experience of the midwife, the distance between the residence of the midwife and the client, the social status of the client and the specific circumstances of the client’s condition. I analyse these factors with regard to home births that were assisted by a certified midwife, using the casebook of a rural Flemish midwife for the period 1831-1892.